Faculty Senate, Annual Report, 2008-2009 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2009)
Valdosta State University. Faculty Senate, Annual Report, 2008-2009. Memorandum. Email to Patrick J. Schloss from Barney "Jay" Rickman, June 2, 2009. Chairperson, Patrick J. Schloss; Vice Chairperson, Louis Levy; Executive Secretary, Barney “Jay” Rickman; Parliamentarian, Cindy Tandy;
1 electronic document. Faculty Senate, Annual Report, 2008-2009. 3 pages.
Keywords: Valdosta State University. Faculty Senate; Electronic records; Committees; Annual reports